The Influence of Leadership Style, Competency and Motivation on Employee Work Productivity at HS Samsoeri Mertojoso Hospital - Sulistyowati, Yekti; Hidayat, Dasrun; Sukajie, Bambang (Universitas Nahdlatul Ulama Sidoarjo, 2024)
The aim of this research was to determine and analyze the influence of leadership style, competence and work motivation which have a dominant influence on employee work productivity at HS Samsoeri Mertojoso Hospital. The research was carried out using a quantitative approach and is included in the type of associative research. The research instrument used a questionnaire. The population is nurses at HS Samsoeri Mertojoso Hospital, totaling 92 people using a total sampling technique. Data analysis was carried out using multiple linear regression analysis techniques using the SPSS program. The research results show that leadership style, competence and work motivation have a significant effect on employee performance. The implications of this research are to increase nurses' work productivity, leaders must be able to set good examples, such as being consistent in implementing policies and being able to make the right decisions. Apart from that, leaders must also be able to be fair to all nurses. Management needs to improve competence, such as by including training and seminars, as well as providing flexibility to pursue higher education.